Policy and Governance Implications for Transition to NTFP-Based Bioeconomy in Kashmir Himalayas - Ishtiyak Ahmad Peerzada (MDPI AG, 2021)
Forests of Jammu and Kashmir (J&K) have a rich diversity of valuable non-timber forest products (NTFP) that local communities extract for their sustenance and income. The region is home to over 60% of species recognized for novel bio-medicinal properties in the Indian Himalayas. There is significant national and international demand for these species, providing income and employment for more than 60% of the population of J&K. Despite this, NTFP are not adequately recognized for their contributions to rural livelihoods and the regional economy due to the lack of appropriate policy and governance mechanisms. In this study, we embrace a bioresource vision to examine challenges and opportunities for transition to a sustainable bioeconomy in J&K. Selected NTFP were considered for valuation to showcase their bioeconomy potential using two approaches. First, we used the ‘market price method’ to estimate the contribution of NTFP to the local economy. Second, the ‘maximum willingness to pay method’ was used to project the bioeconomy potential of NTFP in the region. The analysis reveals that local communities’ revenues could increase by as much as 18 times their current price with appropriate actions to include NTFP. However, to realize this potential, policies and governance frameworks based on increased access and benefit sharing with inclusive institutional models would support the transition of the local economy into a bioeconomy. Fostering public–community partnership by improving the local participation of producers and processors in NTFP value chains for overcoming the existing governance barriers is needed.